Editorial: Youth Digital Activism, Public Policy and Clientelism - Makhasin, Luthfi (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
Youth Digital Activism, Public Policy and Clientelism